Enhanced interfacial and mechanical properties of basalt fiber reinforced poly(aryl ether nitrile ketone) composites by amino-silane coupling agents. (16th September 2021) - Jia, Hang; Liu, Cheng; Qiao, Yue; Zhang, Yu; Dang, Xinxin; Chen, Yousi; Jian, Xigao
Abstract: Basalt fiber (BF) reinforced heat-resistant thermoplastic engineering plastic composites exhibit excellent toughness, strength, corrosion resistance, and high- and low-temperature resistance. However, the BF and resin exhibit poor interfacial compatibility resulting in low interfacial strength. Here, mono-, di- and tri-amino silane coupling agents (3-aminopropyltrimethoxysilane, SATMS; N -(2-aminoethyl)-3-aminopropyltrimethoxysilane, DATMS and (3-trimethoxysilylpropyl)-diethylenetriamine, TATMS) were used to treat BF, and composites were then prepared using the modified BF and high-performance thermoplastic poly(phthalazinone ether nitrile ketone) (PPENK). The chemical structures, surface morphologies, roughness and hydrophilicity of the modified BF surface were characterized. In addition, the flexural strength, tensile strength and interlaminar shear strength of BF-DATMS/PPENK composite increased to 1127 MPa, 633 MPa and 55 MPa, which are 18%, 30% and 25% higher than the desized-BF/PPENK, respectively. And the BF-DATMS/PPENK composite exhibited a glass transition temperature ( T g ) of 293 °C higher than those of PPENK (280 °C) and desized-BF/PPENK (285 °C). Results indicated that the interfacial adhesion between BF and PPENK were improved by the amino-silane modified BF, which in turn enhanced the mechanical properties of the corresponding BF/PPENK composites. Graphical abstract: Image 1 Highlights: Mono-, di-, and tri-aminosilane coupling agents (ASCAs) were used to modify BF. ASCAs possess excellent potential for enhancing interfacial adhesion of BF/PPENK. The BF/PPENK composites exhibit great mechanical and thermo-resistant properties. Di-aminosilne is the best one to increase combination properties of BF/PPENK.